The value of independent component analysis in identifying climate processes - Kent, Michael (Department of Environmental and Geographical Science, 2015)
We find that ICA could make a useful contribution through the identification of the land based seasonal cycle and the ocean based seasonal cycle. These qualities mean that ICA may further prove a useful tool in the problem of identifying components of climate change signals from ensembles of multiple climate models.